A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • 5 years ago

let f(x)=2x^2-3x +1 f'(x)=lim f(x+h) -f(x)/h h->0

  • This Question is Closed
  1. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Replace x with (x+h) -> f(x+h) = 2(x+h)^2 - 3(x+h) + 1 Expand -> f(x+h) = 2x^2 + 4xh + 2h^2 - 3x - 3h +1 subtract original function ->(2x^2+4xh+2h^2-3x-3h+1) - (2x^2-3x+1) add like terms **Notice how some terms will cancel ->4xh + 2h^2-3h Factor out an h -> h(4x + 2h - 3) This is important because now we can cancel the h in the denominator Now re-evaluate the lim of (4x + 2h - 3) as h->0 lim = 4x -3 Hope this helps

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...


  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.